Seasonal expressions of SPAG11A and androgen receptor in the epididymis of the wild ground squirrels (Citellus dauricus Brandt) - Wenyang Yu (European Journal of Histochemistry, 2020)
Sperm-associated antigen 11A (SPAG11A) is expressed exclusively in the epididymis, which can specifically regulate sperm maturation. The aim of this study was to investigate the seasonal expressions of beta-defensin (SPAG11A) and androgen receptor (AR) in the epididymis of the wild ground squirrels (Citellus dauricus Brandt). Morphologically, the results showed that epididymis length and weight in the breeding season were significantly higher than those of the non-breeding season. Histologically, the results revealed that enlarged lumen diameters, thickened epithelial and abundant sperm in the breeding season while reduced lumen diameters and epithelial with no sperm in the non-breeding season. SPAG11A was intensely expressed in cytoplasm and nucleus of epithelial cells in the breeding season, and weaker staining in the non-breeding season. The immunostaining of AR was only presented in nucleus of smooth muscle cells and epithelial cells in the whole epididymis with stronger staining in the breeding season. The results of real-time quantitative PCR also showed that the mRNA levels of SPAG11A and AR in the epididymis during the breeding season were significantly higher than those of the non-breeding season. In addition, the levels of testosterone (T), follicle-stimulating hormone (FSH) and luteinizing hormone (LH) in the serum were higher during the breeding season. Taken together, these results suggested that SPAG11A might play an important role to regulate seasonal changes in epididymal function of the wild ground squirrels.